The names of Homeric heroes: problems and interpretations - Kanavou, Nikoletta (Sozomena, 2015)
"The purpose of this book is to contribute to the appreciation of the linguistic, literary and contextual value of Homeric personal names. It considers both epics and is structured around the character and action of selected heroes in their Homeric contexts. It offers a survey of modern etymologies, set against ancient views, in order to shed light on the parameters surrounding the use of names in Homer and on their reception by ancient audiences." --